Target Proteins in the Dorsal Hippocampal Formation Sustain the Memory-Enhancing and Neuroprotective Effects of Ginkgo biloba - Gaiardo, Renan Barretta; Abreu, Thiago Ferreira; Tashima, Alexandre Keiji; Telles, Monica Marques; Cerutti, Suzete Maria (Frontiers in Pharmacology, 2019)
We have previously shown that standardized extracts of Ginkgo biloba (EGb) modulate fear memory formation, which is associated with CREB-1 (mRNA and protein) upregulation in the dorsal hippocampal formation (dHF), in a dose-dependent manner. Here, we employed proteomic analysis to investigate EGb effects on different protein expression patterns in the dHF, which might be involved in the regulation of CREB activity and the synaptic plasticity required for long-term memory (LTM) formation. Adult male Wistar rats were randomly assigned to four groups (n=6/group) and were submitted to conditioned lick suppression 30 min after vehicle (12% Tween 80) or EGb (0.25; 0.50 and 1.00 g.kg-1) administration (p.o). All rats underwent a retention test session 48 hours after conditioning. Twenty-four hours after the test session, the rats were euthanized via decapitation, and dHF samples were removed for proteome analysis using two-dimensional polyacrylamide gel electrophoresis, followed by peptide mass fingerprinting. In agreement with our previous data, no differences in the suppression ratios were identified among the groups during first trial of CS (conditioned stimulus) presentation (P>0.05). Acute treatment with 0.25 g.kg-1 EGb significantly resulted in retention of original memory, without prevent acquisition of extinction within-session. In addition, our results showed, for the first time, that 32 proteins were affected in the dHF following treatment with 0.25, 0.50 and 1.00 g.kg-1 doses of EGb, which upregulated 7, 19 and 5 proteins, respectively. Additionally, EGb downregulated 2 proteins at each dose. These proteins are correlated with remodelling of the cytoskeleton; the stability, size and shape of dendritic spines; myelin sheath formation; and composition proteins of structures found in the membrane of the somatodendritic and axonal compartments. Our findings suggested that EGb modulates conditioned suppression LTM through differential protein expression profiles, which may be a target for cognitive enhancers and for the prevention or treatment of neurocognitive impairments.